THE ROLES OF BLACK SOYBEAN AND PALM OIL IN CONTROL OF TYPE 2 DIABETES MELITUS - Reno Irwanto; Nela Eska Putri; Nanda Triandita (Universitas Teuku Umar, 2021)
Diabetes mellitus Type 2 (DMT2) is generally caused by a poor diet that causes high glucose in the blood (hyperglycemic) continuously and results in pancreatic dysfunction as a producer of the hormone insulin. The hormone insulin functions as a regulator of the presence of glucose in the blood. Hyperglycemic events can increase the formation of free radicals in the body. Free radicals can increase the damage to the pancreas and other organs in the body, thereby increasing the severity of diabetes. The high mortality rate due to (DMT2) requires serious attention from all parties for its handling. T2DM is a chronic disease that cannot be cured, but can be controlled to reduce the severity of the disease. Foods that are suitable for people with DMT2 are high in protein, vegetable fat, dietary fiber and antioxidants, and have low starch content. Foods sourced from black soybeans can meet the nutrients and antioxidant compounds needed by people with DMT2, because they contain daidzein, genistein, isoflavones, and anthocyanins. Crude palm oil (MSMn) contains carotenoids and vitamin E which can also act as antioxidants. Many studies mention the benefits of black soybeans for people with DMT2, because it can control blood glucose, reduce inflammation, improve blood lipids, increase the antioxidant capacity of blood plasma, and reduce SGOT/SGPT enzymes as markers of liver damage. Functional food for people with DMT2 sourced from black soybeans and MSMn can be black soybean juice enriched with MSMn microencapsulation.